2019
DOI: 10.3847/1538-4365/ab06fb
|View full text |Cite
|
Sign up to set email alerts
|

A 6.7 GHz Methanol Maser Survey. II. Low Galactic Latitudes

Abstract: We report the results of our systematic survey for Galactic 6.7 GHz Class II CH 3 OH maser emission toward a sample of young stellar objects. The survey was conducted with the Shanghai Tianma Radio Telescope (TMRT). The sample consists of 3348 sources selected from the all-sky Wide-Field Infrared Survey Explorer (WISE) point source catalog. We have discussed the selection criteria in detail and the detection results of those at high Galactic latitudes (i.e. |b| > 2 • ) in a previous paper (paper I). Here, we p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(104 citation statements)
references
References 58 publications
10
93
1
Order By: Relevance
“…In Table 1 we present a summary of the longitude ranges, number of masers detected and the publication where these are reported. It is likely that the entire MMB survey accounts for the majority of 6.7 GHz methanol maser sources across the Galaxy, as it has been shown that away from the Galactic plane, methanol maser emission is rare (Yang et al 2017(Yang et al , 2019. Until recently, the integrated flux density for methanol maser sources has been unavailable in the literature, and previous studies have used the peak maser fluxes in order to estimate the corresponding maser luminosities.…”
Section: Methanol Multibeam (Mmb) Surveymentioning
confidence: 99%
“…In Table 1 we present a summary of the longitude ranges, number of masers detected and the publication where these are reported. It is likely that the entire MMB survey accounts for the majority of 6.7 GHz methanol maser sources across the Galaxy, as it has been shown that away from the Galactic plane, methanol maser emission is rare (Yang et al 2017(Yang et al , 2019. Until recently, the integrated flux density for methanol maser sources has been unavailable in the literature, and previous studies have used the peak maser fluxes in order to estimate the corresponding maser luminosities.…”
Section: Methanol Multibeam (Mmb) Surveymentioning
confidence: 99%
“…They observed targets from the all-sky Wide Field Infrared Survey Explorer (WISE) point source catalog that could be associated with 6.7 GHz methanol masers based on their WISE magnitudes. We detected their three new masers and the five already known masers with WISE bright emission listed in Yang et al (2019). The only maser from this catalog not detected by us, likely due to variability, is G81.794+0.911.…”
Section: Comparison With Other Maser Surveysmentioning
confidence: 68%
“…The eight maser sources listed in this catalog within 76 • < l < 83 • and −1 • < b < +2 • were also detected in our survey. More recently, Yang et al (2019) performed a new targeted survey in the whole Galaxy with the 65 m Shanghai Tianma Radio Telescope. They observed targets from the all-sky Wide Field Infrared Survey Explorer (WISE) point source catalog that could be associated with 6.7 GHz methanol masers based on their WISE magnitudes.…”
Section: Comparison With Other Maser Surveysmentioning
confidence: 99%
“…Furthermore, the distribution of these masers can help us study the structure of the spiral arms within the Milky Way. While previous studies already exist, most notably the Methanol Multibeam (MMB) survey (Green et al 2009b) and other surveys (Pestalozzi et al 2005;Pandian et al 2007;Yang et al 2019), our VLA data is the most sensitive (RMS∼18 mJy beam −1 ), thus providing potentially the most complete catalog to date. In addition to the D configuration data, we also have B-configuration data for a large fraction of the survey in order to provide more accurate positions and observations of multiple epochs.…”
Section: 7 Ghz Methanolmentioning
confidence: 99%